ANALYSIS OF THE INFLUENCE OF ORGANIZATIONAL COMMITMENT AND AUDIT COMPLIANCE ON AUDIT QUALITY, AS WELL AS THE ROLE OF THE POSITION GRADE AS MODERATION VARIABLES AT PT BANK INA PERDANA MEDAN Tbk - Totona Berkat Elsuna Zebua; M. Irsan Nasution; Rahima Br. Purba (Yayasan Multidimensi Kreatif, 2025)
The purpose of this study is to partially understand and analyze the influence of auditor organizational commitment and audit compliance on audit quality and auditor position grade, as well as simultaneously to describe and analyze the influence of auditor organizational commitment and audit compliance on audit quality with auditor position grade as a moderation variable. This research is the latest research, where in this study there is one variable that has never been discussed in any research, namely the variable of the auditor's position grade which is able to moderate the variables of the auditor's organizational commitment and the audit compliance variable has a strong influence on audit quality. This research was conducted at PT Bank Ina Perdana with a population and sample of 37 auditors of PT bank Ina Perdana Medan who were formed and have conducted an audit process of PT Bank Ina Perdana. The variables that emerged in this study were the variables of auditor organizational commitment and audit compliance as exogenous variables, audit quality variables as endogenous variables, and position grade variables as moderation variables. The research method using the quantitative descriptive method of data analysis uses the structural equation model (SEM) method, where the results of data processing with the SEM method are carried out using the PLS 3.0 application. According to the results of the study, it can be partially concluded that the variables of auditor organizational commitment and audit compliance affect the audit quality and the grade of the auditor position at PT Bank Ina Perdana Medan. The variable grade of the auditor's position affects the audit quality of PT Bank Ina Perdana Medan. Simultaneously, the variables of organizational commitment and audit compliance affect audit quality with the variable of the auditor's position grade as the moderation variable.